2016
DOI: 10.1097/grf.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum Management of the Obese Gravida

Abstract: Obese women are at increased risk for multiple labor abnormalities, including postdates pregnancy, failed induction of labor, prolonged labor, cesarean delivery, and postpartum hemorrhage (PPH). Prolonged labor among obese women is confined to the first stage of labor. In the setting of reassuring fetal and maternal status, increased time to progress in the first stage of labor should be allowed. Uterine atony occurs more frequently in obese women and vigilance in the prevention of PPH is critical. There is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…After adjustment, the outcomes persisted in the groups with BMI 25-29.9 and 30-34.9. This result is consistent with the results of previous studies [10, 11,13,14,16]. There were less women in G4 compared to the other BMI groups, which could explain why the result isn't significant for these women,.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After adjustment, the outcomes persisted in the groups with BMI 25-29.9 and 30-34.9. This result is consistent with the results of previous studies [10, 11,13,14,16]. There were less women in G4 compared to the other BMI groups, which could explain why the result isn't significant for these women,.…”
Section: Discussionsupporting
confidence: 92%
“…Overweight and obesity are also associated with longer periods of active labor [14]. For cervical ripening and reaching active labor, studies have shown that obese women have a different course of labor compared with women with a normal weight (BMI <25) [7,9,10,13,14]. Cervical ripening is slower, which means that it takes longer to reach the active phase of labor and that they may need more doses of prostaglandins during IOL.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was discovered that apelin has the capacity to inhibit spontaneous and oxytocin-induced uterine contractility [244]. The authors speculated that generally higher apelin concentrations in obese individuals might be responsible for the reduction of uterine contractility in vivo, which put them at increased risk multiple labor complications [244,245]. It was proposed that prolonged fasting could lead to elevation of circulating apelin levels during gestation [246].…”
Section: Other Gestational Complicationsmentioning
confidence: 99%
“…Maternal obesity is a known risk factor for Cesarean delivery in both developed and developing countries; the OR for obese women having a CS delivery compared with women of normal weight is 2.01–2.36 ( 68 , 92 97 ). High maternal BMI is associated with an increased risk for failed labor, which in turn increases labor duration and ultimately leads to CS delivery ( 68 , 92 , 98 ).…”
Section: Confounding Factorsmentioning
confidence: 99%